QUALITY CHARACTERISTICS OF SNAKEHEAD FISHBALL (Channa striata) WITH THE ADDITION OF AGAR-AGAR FLOUR - Rulinda Rulinda; Sumarto Sumarto; Dewita Dewita (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis study aims to determine the effect of adding agar-agar flour to the quality of snakehead fishball. The research method used was an experiment in making snakehead fishball with the addition of commercial agar flour in different quantities. The research design was a non-factorial Completely Randomized Design (CRD) consisting of 4 levels of treatment, namely without adding agar-agar flour (T0), adding agar-agar flour 5 g (T1), 7 g (T2), 9 g (T3). The results showed that the addition of agar-agar (commercial) flour affected significantly at 95% trust rate to the quality of snakehead fishballs. The best treatment is agar-agar flour 9 g in producing quality characteristics of fishball. Fishball has a bright white color; has a distinctive aroma and taste of fish and agar-agar; and chewy texture, cut into two parts (half circle), 69.82% moisture, 0.48% ash, 33.60% protein, 0.15% fat, 39.60% carbohydrates, and 1.60% crude fiber.Keyword: agar-agarflour, fishball, Channa striata